The profile of anxiety, stress, and depression among pharmacy students in Universitas Islam Indonesia - Mutiara Herawati; Aldia Dwi Karinaningrum; Yosi Febrianti (Jurnal Ilmiah Farmasi, 2022)
Abstract Background: Implementation of the new curriculum is tiresome for both lecturers and students. Students who are passive and have limited cognitive abilities will feel depressed. This condition can cause anxiety leading to stress and ultimately depression. The enhancement of graduation standards for apothecary students rises the depression risk factors, especially for retaker students (students who do not pass the Indonesian Pharmacist Competency Exam).Objective: This study aimed to identify the level of anxiety, stress, and depression among undergraduate pharmacy and pharmacist profession students.Method: This study was a cross-sectional design that employed the students of undergraduate and apothecary programs. Respondents involved in this study were undergraduate students in the 2nd, 3rd, and 4th year (n=451) and professional students from batches 35, 36, and 37 (n=271). The DASS 42 questionnaire (Depression Anxiety Stress Scale) was used to identify depression. The data were analyzed descriptively.Result: The number of respondents who met the inclusion criteria was 668. Most undergraduate students had moderate levels of anxiety, normal stress, and normal depression, while apothecary students had normal profiles for all parameters.Conclusion: The various activities and pressure during the learning process triggered psychological disorders for only 5% of respondents.Keywords: Anxiety, stress, depression, DASS-42 Intisari Latar belakang: Implementasi kurikulum baru sangat menguras pikiran dan tenaga, baik dosen maupun mahasiswa. Bagi mahasiswa yang pasif dan memiliki kemampuan kognitif terbatas akan merasakan kondisi tertekan. Kondisi tersebut dapat menyebabkan kecemasan yang meningkat menjadi stress dan pada akhirnya depresi. Peningkatan standar kelulusan mahasiswa apoteker berpotensi meningkatkan faktor risiko kejadian depresi, terutama bagi mahasiswa retaker (mahasiwa yang tidak lulus Ujian Kompetensi Apoteker Indonesia). Tujuan: Penelitian ini bertujuan untuk mengidentifikasi tingkat kecemasan, stress, dan depresi mahasiswa S1 farmasi dan profesi apoteker.Metode: Penelitian menggunakan rancangan cross-sectional kepada mahasiswa program studi farmasi dan profesi apoteker. Responden yang terlibat dalam penelitian ini adalah mahasiswa strata pertama pada tahun ke-2,3, dan 4 (n=451) serta mahasiswa profesi angkatan 35, 36, dan 37 (n=271). Alat yang digunakan untuk mengidentifikasi depresi adalah kuesioner DASS 42 (Depression Anxiety Stress Scale). Data yang diolah secara deskriptif.Hasil: Jumlah responden yang sesuai dengan kriteria inklusi sebanyak 668. Mayoritas mahasiswa S1 memiliki profil tingkat kecemasan sedang, stress normal, dan depresi normal, sedangkan pada mahasiswa profesi apoteker memiliki profil tingkat kecemasan, stress, dan depresi normal. increaseKesimpulan: Dengan berbagai aktivitas dan tekanan selama proses pembelajaran, mayoritas mahasiswa tidak mengalami gangguan psikis, meskipun 5% diantaranya menyatakan mengalami gangguan.Kata kunci : Kecemasan, stress, depresi, DASS-42